Rahn as a Financing Bridge for Business Incubator Tenants: A Case Study on Graduation to Micro and KUR Financing at BSI Ciledug - Teza Kusuma; Nur Fatwa; Nurul Huda (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Business incubator tenants often face limited access to productive financing due to the absence of formal financial records. Under such conditions, Rahn functions as an entry-level liquidity instrument that provides rapid gold-backed funding in compliance with Sharia principles. Nevertheless, the mechanism through which Rahn facilitates graduation to productive schemes such as Micro and KUR financing remains underexplored. This study aims to analyze the role of Rahn in building payment discipline and transaction history, identify key graduation gates, and design a condition-based graduation model grounded in product-contract fit and Sharia governance. A qualitative case study was conducted at BSI Ciledug using semi-structured interviews with branch officials and document analysis of official product guidelines and digital financing manuals. Data were analyzed through thematic coding and source triangulation to ensure validity and analytical rigor. The findings reveal that the graduation process from Rahn to productive financing is condition-based, determined by document completeness, post-Rahn account activity, and branch-level verification. Digital platforms accelerate verification accuracy and transparency, yet human oversight remains essential to uphold Sharia compliance and risk control. The study proposes an audit-ready graduation model that strengthens Sharia financial inclusion and supports the scalability of MSME financing pathways.